Enterprise Innovation, Executive Experience and Internationalization Strategy: Evidence From High-Carbon Industrial Enterprises Versus Low-Carbon Industrial Enterprises in China - Cui, Shuangchang (Frontiers in Energy Research, 2022)
Industrial enterprises are the core subjects to reduce carbon emissions. Their innovations for low-carbon production are the key to determine the effect of carbon emission reduction. This paper examines the impact of executive experience, especially the overseas experience and foreign-language ability, on enterprise innovations across 3559 enterprises in low-carbon, medium-carbon and high-carbon industries respectively. Interestingly, it shows that the executive experience has only played a significant role in enterprise innovations of high-carbon industrial enterprises, indicating that the executive’s international vision might help to promote innovation in high-carbon industry. Then, it is also discovered that there is a mediating effect of international strategy which helps to better understand the impact mechanism of executive experience on enterprise innovation in high-carbon industry.